Diagnostics and Treatment of Enamel Caries in Schoolchildren and Adolescents - Yuldashov F. F.; Ashurova N. G. (Researchparks Publishing, 2021)
The relevance of the study. Caries of temporary and permanent teeth is a massive dental problem for the children's population. At the same time, no other disease is known in medicine that would be so well subjected to prevention and control as caries. Of great importance in the success of a significant reduction of caries in developed countries is the primary prevention of caries, based on the elimination and/or weakening of the main risk factors for this disease, most of which are manageable and are unhealthy lifestyle habits [2.5.7]. The second aspect in reducing the prevalence and intensity of caries is the timely diagnosis of early forms of dental caries (which in the literature are designated by various terms, such as enamel caries, focal demineralization, early stage of caries, initial stage of caries, foci of demineralization, chalky spots) and their competent treatment[1.4.6.8].